The Cunéo and Picot fracture-dislocation of the ankle: A case report and review of the literature. (December 2018) - Klumpp, Raymond; Compagnoni, Riccardo; Zeppieri, Marco; Trevisan, Carlo Lauro
Highlights: The Cunéo and Picot fracture dislocation is an atypical trimalleolar ankle fracture. Fixation of the posterior malleolus is mandatory. Diagnosis can be made from plain X-rays. Fracture instability is not determined by fragment size of the posterior malleolus. Abstract: The Cunéo and Picot fracture-dislocation is an atypical trimalleolar fracture-dislocation of the ankle with unique anatomopathologic and radiographic features, which has not been reported in English literature. We report a case of a 42-year-old woman that was diagnosed with a trimalleolar fracture-dislocation and treated surgically with an open reduction and osteosynthesis of the lateral and medial malleolus. At one-month follow-up, X-rays showed secondary displacement of the medial malleolus requiring revision surgery. The patient complained of persisting pain, with X-rays showing no signs of apparent fracture displacement. A CT scan performed after hardware removal 10 months after trauma showed severe ankle arthritis and fracture malunion at the level of the syndesmosis. The patient was retrospectively diagnosed with a Cunéo and Picot fracture-dislocation. The treatment of trimalleolar fractures is discussed, especially regarding the correct indication of synthesis of the posterior malleolus. Cunéo and Picot fractures are usually inherently unstable even if the posterior malleolar fragment may be small and can easily be recognized from standard X-rays. Whenever this type of fracture is not correctly recognized and managed by osteosynthesis of only the medial and lateral malleolus, clinical outcomes and radiographic follow-ups tend to be unsatisfactory. Fixation of the posterior malleolus is indicated in the management of Cunéo and Picot fractures. Level of clinical evidence: 4.